Avaliação de procedimentos de digestão para determinação voltamétrica de traços metálicos em aminoácidos usados em nutrição parenteral aplicação na determinação de cádmio e chumbo - Carvalho, Claudia Wollmann (2004)
In this work, the interaction of all the amino acids that compose the parenteral nutrition solutions, was investigated with the cadmium and lead metals, with the objective of determining the levels of contamination and if they are important, representing some damage to the patients. There are not data that show the allowed limit of these metals in those solutions, but the Brazilian legislation, through Health Department, stipulates that the maximum cadmium and lead concentration in drinking water can not surpass 5 μg L-1 and 10 μg L-1, respectively. The present work is a contribution to the quantification of Cd and Pb in amino acids solutions that constitute the NP formulations, proposing then, a cleanup method for those samples that allows the determination of Cd and Pb metallic ions through electrochemistries mesurements by voltammetric redissolution. The amino acids are organic compounds that interfere in the determination of the concentration of those metals by voltammetric methods, mainly because of the formation of fort complexes with metals or because of the competition with the metal by the surface of the eletrodo, or, because of the electrochemistry reduction or oxidation of the eletrodo surface. This way, several methodologies were studied, using humid saw digestion, microwaves radiation and UV radiation as pre-treatments of the amino acids samples to reach the complete mineralization of these to viablelize the voltammetric analysis of them. Therefore, to accomplish the voltammetric measurements, it was necessary to work with low amino acids concentrations (Ile, Arg, Leu, Ala, Asp, Orn, Ser, Met, Tyr, Trp, Pro, Cys, Glu, Gly, Thr, Phe, Lys, His, Asn), in solutions that varied from 0,01 to 6 g L-1. The amino acids were individually analyzed and we observed that with the pre-treatment using UV radiation we obtained the best results. Through the pattern addition, we got the largest recoveries of the metals in study. The time of UV irradiation more effective was of eight hours added with hydrogen peroxide and sulfuric acid during the irradiation period. For the phenilalanina, glutamic acid, aspartic acid, treonine, leucine, arginine, cystein and histidine with concentration from 3 to 25% of the usually used in NP formulations, it was possible to determine the cadmium and lead contamination in these amino acids. We found the following concentrations: 0,15 nmol L-1, 38 nmol L-1, 49 nmol L-1, 0,77 μmol L-1, 0,32 μmol L-1, 1,31 μmol L-1, 11,1 nmol L-1, 81,6nmol L-1 respectively of cadmium. In the lead determination we found: 3,04 μmol L-1 in Phe, 53 nmol L-1 in Glu, 42 nmol L-1 in Asp, 0,78 μmol L-1 in Tre, 1,56 μmol L-1 in Arg, 1,4 nmol L-1 in Cys and 21,5 nmol L-1 in His. The origin of this contamination can be attributed to several factors, as to synthesis of the product, packing type (flask and/or covers), sterilization process among others, being necessary an investigation to affirm it certainlly. With the results obtained in the tested pre-treatments, we could conclude that in formulations containing only ornitine, metionine, serine, tyrosine, triptofan and proline is possible to determine directly the cadmium and lead contamination, without using cleanup. The pre-treatment of samples using digestion by UV irradiation were efficient for most of the studied amino acids, which we obtained recovery sign for both metals above 75%. For asparagine, the recovery sign of the metals was below 60%, for isoleucine it was of, approximately, 65%. Among the nineteen amino acids individually analyzed, not all presented contamination of those heavy metals considered toxicant to the organism.